المســاهمة الجنــائيــة في الانتحـــار (Al-Farooq Journal of Sciences, 2026)
A crime may be committed by one person or several people. Multiple participants may be necessary, as in brawls and adultery, or unnecessary, as in murder or theft. Criminal participation in a crime can be either direct or indirect, the latter being called complicity, and the participant is an accomplice.Direct participation in a crime occurs when multiple participants commit a single crime, meaning multiple perpetrators play key roles in committing the same crime. Indirect participation, on the other hand, assumes that one or more persons engage in secondary or incidental activities in committing the crime.However, in some cases, it is difficult to distinguish between direct and indirect participation in suicide.
Keywords: Suicide, Criminal Participation, Criminalization